Experimental Research of Compound Monitoring on Multiple Temporary Blocking Refracturing for Long-Section Horizontal Wells - Zhang, Jingchen; Wu, Baocheng; Wang, Fei; Shi, Shanzhi; Liu, Jinjun; Wang, Mingxing; Li, Jie; Osuji, Nicholas Izuchukwu (Frontiers in Earth Science, 2022)
As an important energy replacement block in China, the tight conglomerate oil fields in Mahu area are characterized by strong heterogeneity, large horizontal stress difference, undeveloped natural fractures, and difficult development. Hence, various new development processes have been tried, including temporary blocking diversion and large section-multiple clusters, etc. In 2020, two adjacent horizontal wells in MD well area had poor fracturing development effect compared with the earlier wells in this area. Analysis suggests that the main reasons are water sensitivity of the reservoir, insufficient fracturing scale or interference from the adjacent old wells. In order to solve this problem, the experiment of multiple temporary plugging and refracturing technology in long horizontal well sections, and electromagnetic -microseismic monitoring were carried out. Because of the different detection principles, there are great differences between the two monitoring results. Fracturing fluid flow diversion is the core of temporary plugging diversion, and accordingly electromagnetic monitoring of fracturing fluid has great advantages in temporary plugging diversion monitoring. The combination of the two approaches provides greater insight than either approach alone, and both approaches require further research and development to address complex situations such as multiple temporary plugging and refracturing in long intervals of adjacent older wells.